Compensatory growth as a response to post-drought in grassland - Zhou, Huailin; Hou, Lulu; Lv, Xiaomin; Yang, Guang; Wang, Yuhui; Wang, Xu (Frontiers in Plant Science, 2022)
Grasslands are structurally and functionally controlled by water availability. Ongoing global change is threatening the sustainability of grassland ecosystems through chronic alterations in climate patterns and resource availability, as well as by the increasing frequency and intensity of anthropogenic perturbations. Compared with many studies on how grassland ecosystems respond during drought, there are far fewer studies focused on grassland dynamics after drought. Compensatory growth, as the ability of plants to offset the adverse effects of environmental or anthropogenic perturbations, is a common phenomenon in grassland. However, compensatory growth induced by drought and its underlying mechanism across grasslands remains not clear. In this review, we provide examples of analogous compensatory growth from different grassland types across drought characteristics (intensity, timing, and duration) and explain the effect of resource availability on compensatory growth and their underlying mechanisms. Based on our review of the literature, a hypothetic framework for integrating plant, root, and microbial responses is also proposed to increase our understanding of compensatory growth after drought. This research will advance our understanding of the mechanisms of grassland ecosystem functioning in response to climate change.